â€œOne-Way-Ticketâ€: When Langston Hughes Traduces the Massive, Absolute and Obligatory Immigration of Today's Africans - Stephane, Beugre Zouankouan (European Scientific Journal, ESJ, 2017)
This paper aims to analyze how Langston Hughes through his poem â€œOne-Way-Ticketâ€ while expressing why blacks were obliged to flee the Big South to the North of the United Sates. He expresses also in a metaphorical and symbolical language many centuries later in the same poem the reasons why and the reality linked to the motivations of todayâ€™s Africans mass immigration towards Europe, the North also. Although separated in time and space, the different characteristics are the same in terms of pull and push factors concerning the past â€œGreat Migrationâ€ and todayâ€™s Africans mass immigration.